Evaluation of Antibacterial Activity and Flavonoid Content of Two Capparis Species from Iran - N Rahimifard; A Shojaii; M Mahbobi; Gh Hafezan; F Bagheri; J Asgarpanah (Institue of Medicinal Plants, ACECR, 2015)
Background: Due to multiple drug resistance against antimicrobial drugs for treatment of infectious disease, investigations to discovering new antibacterial compounds from natural sources have been designated. Objective: According to antimicrobial effects of some Capparis species, this study was carried out to evaluate the antimicrobial activity of the extract and fractions of Capparis cartilaginea and Capparis mucronifolia against 6 bacterial strains. Methods: Aerial parts of the Capparis species were extracted by maceration method using methanol and fractionated separately by liquid-liquid fractionation method. The antibacterial activity of the extract and fractions were studied against 6 bacterial strains using MIC microplate method. Total flavonoid content (TFC) of the extracts and fractions was determined using AlCl3 reagent. Results: The total extract and methanolic fractions of C. mucronifolia were the most effective fractions against the bacterial strains. Methanolic fraction of C. cartilaginea was the most effective fraction with MIC 10.42 µg/ml against Salmonella enterica. The highest antibacterial activity of C.mucronifolia was against Staphylococcus epidermidis with MIC 7.8 µg/ml. Methanolic fractions of Capparis species showed the highest TFC value in AlCl3 colorimetric assay. Conclusion: The results of this study indicate that the extracts and fractions of Capparis cartilaginea and Capparis mucronifolia have antimicrobial effect against 6 gram positive and gram negative strains. According to the high amount of flavonoids in methanolic fraction of C. mucronifolia, the antibacterial activity may be related to the flavonoid compounds of this plant.